210k views
3 votes
Solve for x. 3(x- 4)=15x​

2 Answers

3 votes

Answer:


3(x- 4)=15x


3x-12=15x


3x-12+12=15x+12


3x=15x+12


3x-15x=15x+12-15x


-12x=12


(-12x)/(-12)=(12)/(-12)


x=-1

User Nick R
by
5.4k points
3 votes

Answer:

x=-1

Explanation:

3(x−4)=15x

Use the distributive property to multiply 3 by x−4.

3x−12=15x

Subtract 15x from both sides.

3x−12−15x=0

Combine 3x and −15x to get −12x.

−12x−12=0

Add 12 to both sides. Anything plus zero gives itself.

−12x=12

Divide both sides by −12.

x=

−12

12

Divide 12 by −12 to get −1.

x=−1

User Robert Mikes
by
5.0k points